The Effectiveness of the United Nations Global Compact: Are the Members Advancing the Principles? - James, Gemma (2013)
The United Nations Global Compact (UNGC) has been running since 2000 and has over 10,000 members, including over 7,000 companies, and is a voluntary initiative that seeks to advance ten universal principles. It discloses information on the progress of participants using annual Communications on Progress, which are made publicly available for stakeholder review and analysis. The history of world trade since the Great Depression of the 1920s has shown the recent need for voluntary codes of practice, especially in light of the current economic downturn following the financial crisis. Both companies and countries alike are looking for guidance and to help build trust back up. The UNGC has been criticized for its limited influence on its member companies and lack of disclosure in the annual Communications on Progress (COPs) and it has responded recently by bringing in a Differentiation Programme and providing more guidance for reporting best practice. It still does remain a voluntary initiative and there is a large proportion of currently non-reporting and delisted companies. There is an argument about whether global voluntary codes can ever truly be effective, with good reasoning on both sides. There are some factors which affect their effectiveness such as reaching consensus in formulation and support by governments in order to legitimize the codes. This report takes a sample group of FT500 members of the UNGC and analyses their participation over a period of five years and draws conclusions on how these companies are implementing the UNGC’s principles. The results are summarized as a positive correlation between being based in a European country and the likelihood of participating in the UNGC, possibly due to the explicit support of the scheme by the European Union. There is also a positive correlation between a company's time period in the scheme and the likelihood of being an advanced level participant with more detailed level of disclosure of information, and greater detail of backup for progress. Finally, the reported concluded that by being a member of the UNGC, some companies were advancing the principles and year on year progress has been made, especially in the Advanced level participants. The future looks bright for the UNGC and only time will tell whether the initiative has the motivation, mechanisms and recognition to further advance principles and change the landscape of international business into a more inclusive and sustainable environment.